Qishen Granule Improved Cardiac Remodeling via Balancing M1 and M2 Macrophages - Lu, Wenji; Wang, Qiyan; Sun, Xiaoqian; He, Hao; Wang, Qixin; Wu, Yan; Liu, Yue; Wang, Yong; Li, Chun (Frontiers in Pharmacology, 2019)
Macrophages play a pivotal role in myocardial remodeling (MR) process which could eventually lead to heart failure. Splenic monocytes could be mobilized and recruited under inflammatory conditions and differentiated into different types of macrophages in heart tissues. Inflammatory M1 macrophages could aggravate tissue damage whereas M2 macrophages could promote angiogenesis and tissue repair process. Regulating differentiation and activities of macrophages are attractive strategies for the management of myocardial remodeling. Qishen Granule (QSG) is an effective Chinese medicine for treating heart failure. Our previous studies demonstrated that QSG could inhibit myocardial fibrosis through regulating secretion of cytokines. However, the detailed effects of QSG on recruitment and differentiation of macrophages had not been elucidated yet. In this study, we aimed to explore the effect of QSG on the release of splenic monocytes, the recruitment of monocytes into heart tissues and the differentiation of macrophages under ischemic conditions. Our results showed that QSG could suppress the release of monocytes from the spleen and recruitment of monocytes to heart tissues via inhibiting splenic angiotensin (Ang) II/AT1-cardiac monocyte chemotactic protein (MCP)-1/CC chemokine receptor 2 (CCR2) pathway. The anti-fibrotic effect of QSG was exerted by inhibiting M1 macrophage-activated transforming growth factor (TGF)-β1/Smad3 pathway. Meanwhile, QSG could promote angiogenesis by promoting differentiation of M1 macrophages into M2 macrophages. Our results suggest that compounds of Chinese medicine have synergistic effects on multiple organs and regulating differentiation of monocytes can be a promising target for the management of myocardial remodeling.